(untitled) (Global Journal of Human-Social Science, 2019)
How can cinema be used to understand our society Different sociologists asked throughout history this question Generally they assume that since all subjects act within social institutions films necessarily tell us something about aspects of life in society Besides their visual power and their narratives would be even able to shape our expectations in unconscious ways That s because the social life is presented to us as orderly where people accept prescribed roles that they find satisfactory or unsatisfactory Some of them portray alienation and despair as well as a series of ways in which people face their social conditions and the challenges that life imposes on them In this sense watching a film becomes a sociologically significant event as its experience affects us emotionally psychologically and pedagogically Based on this the paper aims to discuss some sociological perspectives on the relationship between art cinema and society